Efeito do uso de um robô humanoide como ferramenta de motivação para exercícios físicos e seus aspectos psicológicos - Garcia, Guilherme da Silva (2019)
Humanoid robots are robots that generally resemble humans in their structure and communicate with them through gestures and speech. These robots can be used in different functions that require human-robot interaction (HRI), such as motivation to perform physical exercises. Regular exercise and reduction of sedentary behavior is vital for adult health (GARBER et al., 2011). Despite its importance, 62.1% of the Brazilian population does not practice any physical activity (IBGE, 2015). Therefore, the aim of this paper is to investigate the effect of using a humanoid robot as a motivation tool for physical exercise. In order to do this, we utilized a humanoid robot as an instructor for physical exercise in a stationary bicycle. The study was attended by 14 subjects of both genres, with a mean age of 23.5 2.38 years, who were divided into groups: one with the robot instructor, and a control group. These participants performed two exercise sessions, lasting 6 minutes each, and after each session, answered questionnaires about motivation, psychological aspects and human-robot interaction. A sensor was used in the ergometer to measure the distance traveled (km) and the average speed (km / h). For data treatment, descriptive statistics were used to verify frequency, percentage, mean and standard deviation, as well as the Shapiro-Wilk test to test data normality. As for inferential statistics, the T-test and Mann-Whitney were used and the significance level adopted was 5% so that the results were considered significant for p<0.05. The results suggest the robot may have positively influenced the perception of motivation, pleasure and fun. The effort and performance of average speed and distance traveled do not seem to have been influenced. The interaction with the robot also seems to have generated a positive change in the moods of the participants. The comparisons made, however, did not show a statistically significant difference. We believe that a larger number of participants and other studies are needed to conclude about the robot influence on the investigated aspects. Future studies includes using the robot to motivate patients in clinics and hospitals and a long-term application of this tool.